John Buridan on the Possibility of Defining Definition. Issue 3 (3rd July 2017) - Guerizoli, Rodrigo
Abstract : The study of the medieval reception of Aristotle's Topics has largely been oriented toward debates on dialectical argumentation. And this is surely right. Nonetheless, I wish to approach John Buridan's commentary on the Topics from another perspective, which highlights some semantic features of the set of predicates around which the work is organized. Thus, in my paper I will first reconstruct Buridan's account of the identification of the predicates discussed in the Topics . I will argue that, for him, they are different in that they reflect one or more features of the way in which definiens and definiendum relate. By doing this, I will shed light on the role the notion of definition plays in Buridan's commentary, so that an interpretation of it as a work on definition becomes promising. In the second part of the paper, I will offer an analysis of Buridan's first move in his commentary toward a theory of definition. It concerns the problem of whether there is a definition of definition. In examining Buridan's answer, I will argue for the close connection between his treatment of definitions and his theory of supposition, so that distinctions among the different modes of supposition help him to disambiguate statements in their possible meanings, and thus to clarify the difficulty related to the definability of definition.